Studies on trypanosome-resistant cattle. I. The breeding and growth performance of N'Dama, Muturu and zebu cattle maintained under the same conditions of husbandry - Roberts, C.J.; Gray, A.R. (Springer, 1973)
The breeding and growth performances of N'Dama, Muturu and zebu cattle were investigated to determine trypanosome resistance of the breeding stock. Data on age at first calving, calving interval, calf birth weight and growth rate included.